Unsuccessful external validation of the MAC-score for predicting increased MIB-1 index in patients with spinal meningiomas - El-Hajj, Victor Gabriel; Fletcher-Sandersjöö, Alexander; Pettersson-Segerlind, Jenny; Edström, Erik; Elmi-Terander, Adrian (Frontiers in Oncology, 2022)
Objective Recently, the MAC-spinal meningioma score (MAC-score) was proposed to preoperatively identify spinal meningioma patients with high MIB-1 indices. Risk factors were age ≥ 65 years, a modified McCormick score (mMCs) ≥ 2, and absence of tumor calcification. The aim of this study was to externally validate the MAC-score in an independent cohort. Methods Using the same inclusion and exclusion criteria as in the original study, we performed a retrospective, single-center, population-based, cohort study that included patients who had undergone surgical treatment for spinal meningiomas between 2005 – 2017. Data was collected from patient charts and radiographic images. Validation was performed by applying the MAC-score to our cohort and evaluating the area under the receiver operating characteristic curve (AUC). Results In total, 108 patients were included. Baseline and outcome data were comparable to the original development study. An increased MIB-1 index (≥5%) was observed in 56 (52%) patients. AUC of the MAC-score in our validation cohort was 0.61 (95% CI: 0.51 – 0.71), which corresponds to a poor discriminative ability. Conclusion The MAC-score showed poor discriminative ability for MIB-1 index prediction in patients with spinal meningiomas. Moreover, the MAC-score rests on a weak theoretical and statistical foundation. Consequently, we argue against its clinical implementation.